2019
DOI: 10.1002/cne.24700
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin immunoreactive neurons in the basolateral amygdala of the rhesus monkey (Macaca mulatta)

Abstract: Several distinct subpopulations of interneurons (INs) in the amygdalar basolateral nuclear complex (BNC) of the rat can be recognized on the basis of their expression of calcium‐binding proteins and neuropeptides, including parvalbumin (PV), somatostatin (SOM), calretinin (CR), and cholecystokinin (CCK). In the rat BNC CCK is expressed in two separate IN subpopulations, termed large (CCKL) and small (CCKS). These subpopulations exhibit distinct connections indicative of discrete functional roles in the circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In the BLA, CCK/CB1 basket cells are also present both in the rodent (Katona et al, 2001 ; McDonald and Mascagni, 2001 ; Vereczki et al, 2016 ; Rovira-Esteban et al, 2017 ) and in the monkey (McDonald, 2021 ), giving rise to 0.9% of all neurons in the LA and 2.1% in the BA in the mouse BLA (Vereczki et al, 2021 ). CCK/CB1 basket cells typically have large somata and multipolar dendritic trees both in rodents (Mascagni and McDonald, 2003 ; Vereczki et al, 2016 ; Rovira-Esteban et al, 2017 ) and monkey (McDonald and Mascagni, 2019 ). The neurochemical content of CCK/CB1 basket cells is variable, as they may express vesicular glutamate transporter type 3 (VGluT3) and Calb in largely non-overlapping subpopulations (Omiya et al, 2015 ; Rovira-Esteban et al, 2017 ).…”
Section: Perisomatic Inhibition In Cortical Regions Originates From Three Interneuron Typesmentioning
confidence: 99%
“…In the BLA, CCK/CB1 basket cells are also present both in the rodent (Katona et al, 2001 ; McDonald and Mascagni, 2001 ; Vereczki et al, 2016 ; Rovira-Esteban et al, 2017 ) and in the monkey (McDonald, 2021 ), giving rise to 0.9% of all neurons in the LA and 2.1% in the BA in the mouse BLA (Vereczki et al, 2021 ). CCK/CB1 basket cells typically have large somata and multipolar dendritic trees both in rodents (Mascagni and McDonald, 2003 ; Vereczki et al, 2016 ; Rovira-Esteban et al, 2017 ) and monkey (McDonald and Mascagni, 2019 ). The neurochemical content of CCK/CB1 basket cells is variable, as they may express vesicular glutamate transporter type 3 (VGluT3) and Calb in largely non-overlapping subpopulations (Omiya et al, 2015 ; Rovira-Esteban et al, 2017 ).…”
Section: Perisomatic Inhibition In Cortical Regions Originates From Three Interneuron Typesmentioning
confidence: 99%
“…Electron microscopic studies in rat have demonstrated that 10% of m1R+ axon terminals in the BNC form symmetrical synapses. The main postsynaptic targets of these m1R+ axon terminals are somata, axon initial segments, and thick proximal dendrites of PNs, which are the same structures targeted by many GABAergic INs, especially PV and CCK INs (McDonald et al, 2002; McDonald & Augustine, 2020; McDonald & Mascagni, 2019; Pitkänen & Amaral, 1993; Vereczki et al, 2016). Although neuromodulatory (i.e., dopaminergic, noradrenergic, serotonergic, or cholinergic) inputs to the BNC also form symmetrical synapses, their main postsynaptic targets are distal dendrites and spines of PNs (McDonald, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, immunohistochemical studies of NPNs in the BNC of human and nonhuman primates have shown that subpopulations of these neurons express the calcium‐binding proteins PV (Pantazopoulos, Lange, Hassinger, & Berretta, ; Pitkänen & Amaral, ; Sorvari et al, ), CB (Pantazopoulos et al, ; Pitkänen & Amaral, ; Sorvari et al, ) and CR (McDonald, ; Sorvari et al, ), as well as the neuropeptides SOM (Amaral et al, ; Desjardins & Parent, ; McDonald et al, ; Schwartzberg, Unger, Weindl, & Lange, ), NPY (McDonald et al, ; Schwartzberg et al, ), and CCK (McDonald & Mascagni, ). The same morphological diversity of NPNs seen in the present Golgi study was also observed in the immunohistochemical studies of each of these calcium binding proteins and neuropeptides in primates.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence from light and electron microscopic studies in rodents and primates that different NPN subpopulations have different postsynaptic targets, and thus play specific roles in the circuitry of the BNC (McDonald, ). In both rodents (Bienvenu et al, ; Vereczki et al, ) and primates (Pitkänen & Amaral, ; Sorvari et al, ; McDonald & Mascagni, ), two separate GABAergic subpopulations, PV+ and CCK+ NPNs, are basket cells that innervate the soma and proximal dendrites of PNs. Remarkably, although a high density of pericellular baskets contacting PN somata are observed in the BNC in immunohistochemical studies of all species studied using antibodies to GABA, PV, or CCK, to the authors' knowledge they have not been described in Golgi studies of the BNC in any species, including the present study.…”
Section: Discussionmentioning
confidence: 99%